The Commission for Environmental Cooperation as a model for promoting sustainable development in the Americas. (25th April 2011) - Mumme, Stephen P.; Lybecker, Donna
The North American Commission for Environmental Cooperation (CEC) has been touted as a regional model for strengthening environmental cooperation and sustainable development related to free trade regimes. This study reviews CEC's development since 1994 in the context of its ambitious North American Free Trade Agreement related mandate. Drawing on its own documents, government records and scholarly assessments, the study traces the CEC's steady decline in response to limited support by its member governments. The CEC has nevertheless gained a valuable niche in North American environmental management, spotlighting problems, strengthening public participation and building capacity for environmental cooperation in critical areas of regional environmental importance. Thus we argue the CEC is at least a partial template for building environmental protection into free trade agreements in the hemisphere. Future agreements should be informed by the CEC's shortcomings as well as its successes if they wish to strengthen trade-related environmental protection in the Americas.